Morphological Diagnoses of Higher-Level Phyllostomid Taxa (Chiroptera: Phyllostomidae) (2016)
ABSTRACT: Phyllostomidae (New World leaf-nosed bats), the second most speciose chiropteran family, is one of the best-known and well- studied chiropteran groups. Due to the ecological and morphological diversity of this family, comparative studies of phyllostomids abound in the literature, and numerous systematic and phylogenetic analyses have been published. Unfortunately, many of these studies have reached different conclusions concerning phyllostomid relationships, and have proposed different classification schemes. This has led to confusion, and highlighted the need for a well-supported and stable classification of the family, particularly at the level of subfamilies and tribes, areas of the greatest controversy. The goal of this paper is to provide morphological diagnoses of higher-level taxa (subtribes, tribes, and subfamilies). Herein we provide morphological diagnoses for 11 subfamilies (Macrotinae, Micronycterinae, Desmodontinae, Lonchorhininae, Phyllostominae, Glyphonycterinae, Glossophaginae, Lonchophyllinae, Carollinae, Rhinophyllinae, and Stenodermatinae), 12 tribes (Desmodontini, Diphyllini, Macrophyllini, Phyllostomini, Vampyrini, Choeronycterini, Glossophagini, Brachyphyllini, Lonchophyllini, Hsunycterini, Sturnirini, and Stenodermatini), and nine subtribes (Anourina, Choeronycterina, Brachyphyllina, Phyllonycterina, Vampyressina, Enchisthenina, Ectophyllina, Artibeina, and Stenodermatina).